DAMPAK PENGGUNAAN TIKTOKSHOP TERHADAP GAYA HIDUP PADA GENERASI Z MENURUT PERSPEKTIF EKONOMI ISLAM (Studi Pada Mahasiswa Gen Z di Universitas Islam Negeri Fatmawati Sukarno Bengkulu) - Ade Ihwani Harahap; Setiawan, Romi Adetio; Anwar Junaidi (JSE: Jurnal Sharia Economica, 2026)
The development of social commerce through the TikTok platform has changed Generation Z consumption patterns, particularly in their impulsive online shopping behavior. This study aims to analyze the influence of TikTok use on the consumer lifestyle of Generation Z students and its impact on financial management, from an Islamic economic perspective. This study used a quantitative approach with a survey method. Data were obtained from 82 respondents, students from the Faculty of Islamic Economics and Business, Fatmawati Sukarno State Islamic University, Bengkulu, from the class of 2021 who actively use TikTok. Data analysis techniques used validity, reliability, normality tests, and partial t-tests using SPSS. The results showed that TikTok use had a positive and significant effect on the consumer lifestyle of Generation Z students. Furthermore, a consumer lifestyle had a significant effect on student financial management. A consumer lifestyle was also shown to mediate the influence of TikTok use on financial management. From an Islamic economic perspective, these findings indicate that uncontrolled consumer behavior has the potential to conflict with the principles of simplicity and wise wealth management. Therefore, it is necessary to increase Islamic financial literacy so that the use of TikTok Shop remains in line with Islamic values.